Pengaruh Hari Perdagangan Terhadap Return Saham Di Bursa Efek Jakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
ABSTRACT The objectives of this study are: (1) to test the effect of trading days on stock return, (2) to determine whether there is any differences of daily stock returns, and (3) to test daily abnormal return of some Indonesians common stocks. The results indicate that there is an effect of trading days on stock return. The study also shows that there is the difference in daily stock returns. Finally, the result of the study indicates that Tuesday and Wednesday have an abnormal return.